1999
DOI: 10.1111/1468-0009.00125
|View full text |Cite
|
Sign up to set email alerts
|

Five Laws for Integrating Medical and Social Services: Lessons from the United States and the United Kingdom

Abstract: Because persons with disabilities (PWDs) use health and social services extensively, both the United States and the United Kingdom have begun to integrate care across systems. Initiatives in these two countries are examined within the context of the reality that personal needs and use of systems differ by age and by type and severity of disability. The lessons derived from this scrutiny are presented in the form of five "laws" of integration. These laws identify three levels of integration, point to alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
571
1
28

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(608 citation statements)
references
References 34 publications
8
571
1
28
Order By: Relevance
“…Whether or not these improved health outcomes can be achieved within the existing cost structures available for the care of patients with chronic illness is yet to be definitively determined. 13 Whatever may be the outcome of our experiments with coordinated care and chronic disease self-management programs, the Australian health system appears to be no longer able to afford to deliver costly acute health services at the current rate of escalation. Strategies therefore need to be found to reduce demand for acute care services, especially when this demand can be moderated through early intervention programs.…”
Section: Cdsm Strategiesmentioning
confidence: 99%
“…Whether or not these improved health outcomes can be achieved within the existing cost structures available for the care of patients with chronic illness is yet to be definitively determined. 13 Whatever may be the outcome of our experiments with coordinated care and chronic disease self-management programs, the Australian health system appears to be no longer able to afford to deliver costly acute health services at the current rate of escalation. Strategies therefore need to be found to reduce demand for acute care services, especially when this demand can be moderated through early intervention programs.…”
Section: Cdsm Strategiesmentioning
confidence: 99%
“…Integration was seen to be the development of more comprehensive approaches to care provision that depended on formal relationships or structural arrangements to organise and deliver that care. This working definition drew upon the key differences identified by Leutz (1999 …”
mentioning
confidence: 99%
“…The WHO 4 has argued that integrating health services can be adversely affected 9 in a national study of GP and hospital integration, found that stakeholder involvement, leadership and change agent characteristics, time and flexibility, resources and incentives and communication were critical integration success factors. Leutz 10 devised five "laws of integration" from his extensive experiences with integrated health services in the United Kingdom and United States: 1. Seek to assist the neediest clients without disadvantaging any other groups; 2.…”
Section: The Difficultiesmentioning
confidence: 99%